Implementation of Visual Media in Improving Understanding of Religious Education in Children in Group ARaudhatul Athfal Aman Sentosa Sekuduk Village - Sera Yuliantini; Ozy Anggrean (ADISAM Publisher, 2023)
assessments in accordance with the RPPH and carrying out follow-up activities. 2) The obstacle in implementing visual media in increasing understanding of religious education in children in group A Raudhatul Athfal Aman Sentosa Sekuduk Village is that not all educators are able to create and use visual media creatively so that there are students who are less interested in participating in learning activities and the conditions of students which is not conducive. 3) The teacher's efforts to overcome obstacles to the implementation of visual media in increasing understanding of religious education in children in group A Raudhatul Athfal Aman Sentosa Sekuduk Village are always practicing in making and using visual media, establishing collaboration between educators both from within the school and educators from other schools and using several types of visual media and methods in learning activities